-6(10-4r)=-3(-12-8f)

Simple and best practice solution for -6(10-4r)=-3(-12-8f) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(10-4r)=-3(-12-8f) equation:


Simplifying
-6(10 + -4r) = -3(-12 + -8f)
(10 * -6 + -4r * -6) = -3(-12 + -8f)
(-60 + 24r) = -3(-12 + -8f)
-60 + 24r = (-12 * -3 + -8f * -3)
-60 + 24r = (36 + 24f)

Solving
-60 + 24r = 36 + 24f

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '60' to each side of the equation.
-60 + 60 + 24r = 36 + 60 + 24f

Combine like terms: -60 + 60 = 0
0 + 24r = 36 + 60 + 24f
24r = 36 + 60 + 24f

Combine like terms: 36 + 60 = 96
24r = 96 + 24f

Divide each side by '24'.
r = 4 + f

Simplifying
r = 4 + f

See similar equations:

| 10x+7-2x=x-2+8x | | 10x+7=x-2+8x | | 12-10(5x+4)+4x= | | 16*5*3.14= | | 3.14*16*5= | | 6b+4-2b=6b | | (2x+8)(3x+24)=0 | | 90+x+34+x+64=180 | | -6x^3+9x^2+6x= | | .5y-4=33.33y-3 | | y-3x=-5y | | 5x+10=5x-10 | | 23b+70=40b-100 | | 12a+95=26a-87 | | a+56=3a+46 | | 3mn^3/14x^2y/9n^4/7x^4y^3 | | 6-2x^2=0 | | 15u+80=71u-88 | | 22s-64=15s+13 | | 2w+82=32w-98 | | ax=7-bx | | 11b+30=30b-84 | | 31m-4=21m+76 | | -6x-42=-35 | | 42f-100=27f-25 | | h+76=2h+23 | | 2/4(x+8)=1/3(x+27) | | (6x-3)+2=5x | | 4k-4k-1=48 | | (3z-8)(z+5)=0 | | -2t+11t+(5+-9)t= | | -1/4+-3/4= |

Equations solver categories